PSYCHOSOMATIC SYNDROME (ResearchJet Journal of Analysis and Inventions, 2021)
One type of neurological disease is psychosomatic syndrome. Psychosomatic syndrome is a disease characterized by impaired visceral function as a result of mental stress. Let's get acquainted with some of them. We will focus on the question of what is pain in the heart area or psychogenic cardialgia.